An updated study of the magnetic fraction in medicinal sediments from two Peruvian lagoons - Cerón, María (2020)
We studied diverse minerals found in the magnetic fraction of clays from medicinal sediments collected in two Peruvian lagoons, La Milagrosa (MML) and La Mellicera (MELL). The clay fraction was separated by the sedimentation method. The analytical physical techniques we used were energy dispersive X-ray fluorescence (EDXRF), X-ray diffractometry (XRD) and transmission Mössbauer spectroscopy (TMS). We complemented them with a physical chemical analysis to determine texture, pH and electrical conductivity. We have observed, via XRD, minerals such as illite, calcite and maghemite. Specically, for MML, by XRD we observed two minerals phases: quartz and dolomite. TMS allowed us to observe the magnetic fraction of the sediments. In the spectra we observed four magnetic sextets and three paramagnetic doublets. The sextets were assigned to hematite/goethite, two sites of magnetite (Fe3+ and Fe2.5+) and maghemite. L